Structural change in times of increasing openness: Assessing path dependency in European economic integration - Claudius Gräbner; Philipp Heimberger; Jakob Kapeller; Bernhard Schütz (Johannes Kepler University Linz, Institute for Comprehensive Analysis of the Economy (ICAE), 2018)
This paper analyzes the dynamics of structural polarization and macroeconomic convergence vs. divergence in the context of European integration, where the latter is understood primarily as an increase in economic and financial openness. In the process of estimating the dynamic effects of openness shocks on 26 EU countries, we develop a taxonomy of European economies that consists of core, periphery, financialized and Eastern European catch-up economies. As these four country groups have responded in a distinct way to the openness shocks imposed by European integration, we argue that the latter should be seen as an evolutionary process that has given rise to different path-dependent developmental trajectories. These trajectories relate to the sectoral development of European economies and the evolution of their technological capabilities. We propose a set of interrelated policy measures to counteract structural polarization and to promote macroeconomic convergence in Europe.
Keywords: 330; Wirtschaftliche Konvergenz; Europäische Integration; Pfadabhängigkeit; Wettbewerb; EU-Staaten